Havia um CAPS no meio do caminho: adoecimento mental, narrativa e produção de sentido - Valentim, Farley Janusio Rebouças (2011)
This research aims to investigate ways through which users of a Psychosocial Care Center - CAPS make sense of their illness, addressing the biographical narratives produced by these. This work starts from two premises. First, the biographical narratives are a way to give meaning to their life and are able to express our experiences, organizing them in an orderly and rational discourse. Second, the emergence of certain painful experiences such as the emergence of mental disorders and their consequences (diagnosis and treatment) may be relevant biographical processes, since factors usually act as "disorder" important, compelling the person to give direction of such changes. Thus, it develops here a study on the narrative, based on theoretical and methodological approach of discursive practices and production of meanings, and a constructionist perspective, which sees social reality as a co-construction, historically and culturally located, which gives through the use of language made by speakers as they interact each other. The rise of mental illness as a factor relevant biographical impels the person to deal with such experience, stimulating new stories about himself, whose construction is through the interactions and social contexts which is part of the narrator. The development of research, we focused on the qualitative approach, with two interviews with users of a CAPS. It was used as a model Interview Narrative, proposed by Schultz. The interviews were transcribed and analyzed in order to understand the forms and mechanisms used by users to deal with the effects of illness on their lives and build a sense for this, trading it in various contexts in which they travel. Recognize the multiple possibilities and influences that revolve around the production of meaning in the construction of biographical narratives of CAPS users is a way to reflect on current practices of care, rethinking the notions and concepts that underlie them. Thus, beyond the status of academic production, this paper hopes to foster the development of new ways to understand and act against those who are suffering from mental disorders, seeking to address more broadly the ways in which this experience and deals with the onset of symptoms serving as a subsidy for the construction of further research to keep alive the questions about the work done in CAPS.